Determination of Anti-Bacterial Activity Using Houttuynia Cordata Thunb. Ethanol Extract - Lai, Mei Wei (2015)
The aim of the study in this project is to assess the anti-bacterial effect of dried Houttuynia cordata Thunb ethanolic extract against Escherichia coli, Bacillus subtilis and Staphyloococcus aureus. The extract of medicinal plants were prepared with using conventional method by starting step of pulverized or grounded dried Houttuynia cordata Thunb to coarse powders, then suspended herb in 95% ethanol for 7 days. After that, filtration and evaporation of ethanol, the remaining extracts were oven-dried at 60 °C. For experimental preparation, each extract was re-dissolved in its own solvent to give the desired concentration. Serial dilution of various concentration of Houttuynia cordataThunb ethanolic extract, 200mg/ml, 100mg/ml, 50mg/ml, 25mg/ml, 12.5mg/ml, 6.25mg/ml, 3.125mg/ml was prepared. The anti-bacterial activities of Houttuynia cordata thumb ethanolic extracts were evaluated using the Kirby Bauer Disk Diffusion Method and the inhibitory zones were recorded in millimeters. Control negative, 95% ethanol and control positive, Gentamicin were assessed using Kirby Bauer Disk Diffusion Method. The results of this study showed that various concentration of Houttuynia cordata Thunb ethanolic extracts against E. coli, B. subtilis and S. aures were showed to anti-bacterial activity. Gentamicin showed zone of inhibition towards E. coli, B. subtilis and S. aureus with zone inhibition of 20.45333 ± SD 2.793230, 19.54333± SD 0.933293 and 22.10667 ± SD 0.323968 respectively. Negative result of Houttuynia cordata Thunb ethanolic extract suggest a problem may due to potential factor and limitation.